Methylation-based reclassification and risk stratification of skull-base chordomas - Huo, Xulei; Guo, Tengxian; Wang, Ke; Yao, Bohan; Li, Da; Li, Huan; Chen, Wei; Wang, Liang; Wu, Zhen (Frontiers in Oncology, 2022)
Background: Skull base chordomas are rare malignant bone cancers originating from the remnant of the notochord. Survival is variable, and clinical or molecular factors cannot reliably predict their outcomes. This study therefore identified epigenetic subtypes that defined new chordoma epigenetic profiles and their corresponding characteristics. Methods: Methylation profiles of 46 chordoma-resected neoplasms between 2008 and 2014, along with clinical information, were collected. K-means consensus clustering and principal component analysis were used to identify and validate the clusters. The ssGSEA analysis, methylCIBERSORT algorithm, and copy number analysis were used to identify characteristics of the clusters. Results: Unsupervised clustering analysis confirmed two clusters with a progression-free survival difference. Gene set enrichment analysis indicated that the early and late estrogen response pathways and hypoxia pathway were activated, while the inflammatory and interferon gamma responses were suppressed. Forty-six potential therapeutic targets corresponding to differentially methylated sites were identified from chordoma patients. Subgroups with a worse outcome were characterized by low immune cell inﬁltration, higher tumor purity, and higher stemness indices. Moreover, copy number amplifications mostly occurred in cluster 1 tumors and the high risk group. Additionally, the presence of a CCNE1 deletion was exclusively found in better outcome chordoma patients, while RB1 and CDKN2A/2B deletions were mainly found in worse outcome chordoma patients. Conclusions: Chordoma prognostic epigenetic subtypes were identified and their corresponding characteristics were found to be variable.